Intraoperative Imaging of Positron Emission Tomographic Radiotracers Using Cerenkov Luminescence Emissions - Jason P. Holland; Guillaume Normand; Alessandro Ruggiero; Jason S. Lewis; Jan Grimm (Molecular Imaging)
Imaging the location and extent of cancer provides invaluable information before, during, and after surgery. The majority of “image-guided” methods that use, for example, positron emission tomography (PET) involve preoperative imaging and do not provide real-time information during surgery. It is now well established that the inherent optical emissions (Cerenkov radiation) from various β-emitting radionuclides can be visualized by Cerenkov luminescence imaging (CLI). Here we report the full characterization of CLI using the positron-emitting radiotracer 89 Zr-DFO-trastuzumab for target-specific, quantitative imaging of HER2/neu -positive tumors in vivo. We also provide the first demonstration of the feasibility of using CLI for true image-guided, intraoperative surgical resection of tumors. Analysis of optical CLIs provided accurate, quantitative information on radiotracer biodistribution and tissue uptake that correlated well with the concordant PET images. CLI, PET, and biodistribution studies revealed target-specific uptake of 89 Zr-DFO-trastuzumab in BT-474 ( HER2/neu positive) versus MDA-MB-468 ( HER2/neu negative) xenografts in the same mice. Competitive inhibition (blocking) studies followed by CLI also confirmed the in vivo immunoreactivity and specificity of 89 Zr-DFO-trastuzumab for HER2/neu . Overall, these results strongly support the continued development of CLI as a preclinical and possible clinical tool for use in molecular imaging and surgical procedures for accurately defining tumor margins.